The Effect of Transformational Leadership on Performance of Organizations: A Review of Systematic Literature Across Different Sectors - Pandia, Nadia Erlikasna Br; Meilani, Yohana Cahya F. Palupi (Universitas Nahdlatul Ulama Sidoarjo, 2024)
In many organizational sectors, transformational leadership has been recognized as a leadership style that greatly affects worker performance and job satisfaction. The objective of this systematic assessment of the literature is to explore how transformational leadership impacts organizational performance. This research shows that there is a positive relationship between employee performance and transformative leadership, using a review of studies undertaken in different contexts and sectors. Additionally, this review highlights aspects of organizational performance that are influenced by transformational leadership. These findings confirm the transformative potential of transformational leadership in a variety of organizational settings and provide insight for leaders aiming to foster productive work environments.